Controlling strength and ductility: Dislocation-based model of necking instability and its verification for ultrafine grain 316L steel. (March 2016) - Vinogradov, A.; Yasnikov, I.S.; Matsuyama, H.; Uchida, M.; Kaneko, Y.; Estrin, Y.
Abstract: A phenomenological dislocation-based approach is proposed to account for the necking phenomenon during tensile deformation of metals and alloys. The critical strain corresponding to the onset of tensile instability is predicted in a simple explicit form based on the Kocks-Mecking dislocation kinetics approach. The model strongly suggests that uniform elongation is controlled primarily by the rate of dislocation recovery. The role of the stain rate sensitivity in stabilizing uniform plastic flow is also elucidated. Model predictions are found to be in excellent agreement with experimental data obtained for ultrafine grained 316L steel produced by severe plastic deformation. The approach presented provides general ques for designing materials with enhanced ductility, including ultrafine grained and bulk nanostructured metals and alloys. The proposed recipe is based on microstructural control of the rate of dynamic recovery of dislocation. Graphical abstract: